A Piece of Paper and a Pair of Scissors - Claudiu Mihai; Christine Rakowski (Journal of Basic & Applied Sciences, 2014)
In this paper we will discuss the problem of splitting a given geometrical figure in two regions of equal area by drawing a line through a given point in the interior of the figure. For some geometric figures we will further discuss the possibility of splitting the figure in regions with areas p% and (100-p) %.